Understanding the disease burden and unmet needs among patients with cutaneous lupus erythematosus: A qualitative study - M.E. Ogunsanya, BPharm, PhD; C.M. Brown, PhD; D. Lin; F. Imarhia; C. Maxey; B.F. Chong, PhD (Wolters Kluwer, 2018)
Background: Cutaneous lupus erythematosus (CLE) is a rare dermatologic autoimmune disease marked by photosensitive lesions that can vary in appearance depending on the subtype. The extent to which CLE affects a patient's quality of life (QoL) has not been fully characterized. Focus groups were conducted to explore patients' perspectives of how CLE has affected their lives and to understand the unmet needs in regards to CLE treatment and care. Methods: This qualitative study involved three focus groups with a total of 19 patients with CLE. A moderator guide containing open-ended questions was used to assess how CLE affects overall QoL. The focus groups were audio-recorded with notetaking. Data were content-analyzed to identify emergent themes. Results: Four themes emerged as important to patients with CLE: disease sequelae, social interactions, functioning, and unmet needs. Most patients reported decreased QoL due to signs and symptoms such as dyspigmentation and scarring. Having CLE negatively affected patients' mental health and personal relationships and led to negative coping strategies, such as recreational drug use. Issues related to body image were also elicited by patients. Patients cited unmet needs including lack of treatments to improve chronic skin lesions of CLE and inadequate patient education on living with CLE. Conclusions: Providers can look for signs of QoL impairment in patients with CLE by asking questions related to body image, mental health, social isolation, and coping mechanisms. Future QoL measures can include the effect of CLE-specific attributes such as scarring and dyspigmentation to empower patients' voices in determining therapeutic efficacy in future clinical trials. Findings from our study have added a new understanding of daily experiences that were elicited directly from patients with CLE. Keywords: cutaneous lupus erythematosus, outcomes, unmet needs, qualitative, focus group, burden, quality of life